Validation of certain family, generic and species names in Krapp-Schickel & Müller, 2011 and Lowry & Myers, 2013 - Lowry, J. K.; Myers, A. A. (Zootaxa, 2013)
Krapp-Schickel & Müller (2011) published one new genus Kairos and two new species, Kairos segregans and Elasmopus polynesus in Marine Biodiversity Records. Because Marine Biodiversity Records is an entirely electronic journal which does not produce hard copies, it is not eligible to publish new taxonomic names unless the names are registered in Zoobank and cited in the paper at the time of publication. Consequently, the genus Kairos and the species Kairos segregans and Elasmopus polynesus are currently considered to be nomina nuda. Unaware of this, Lowry & Myers (2013) established the family Kairosidae based on the genus Kairos. Because the family is based on an unavailable name, it also becomes a nomen nudum.